Editing, directing, and The Cool World: filmmaking as a choreographic art. Issue 10 (3rd October 2021) - Pearlman, Karen
ABSTRACT: Given that cinema is a movement-based art form, this article proposes that a director's work is more analogous to that of a choreographer than that of an author. From there, it considers others involved in choreographing a film's movement and focusses on the film editor. The case study for revealing how directing and editing shape cinematic movement is The Cool World (1963), a radical and insufficiently recognised film directed and edited by Shirley Clarke. My analysis looks closely at a specific passage in the film to identify how its movement-phrases, as shaped in editing, convey or create experiences of community, space, and subtext – experiences that cannot be created on paper or even in shots until the shots are edited. Through this case study of a director-editor, I demonstrate that editing is a process of authoring the movement-phrases that move the spectator. Having considered editing as an intrinsic part of Clarke's directorial agency, I conclude with brief consideration of the question: if we understand a film to be at least in part 'authored' in editing when the director and editor are one person, what happens when they are not?